Decision support systems : a knowledge-based approach - Holsapple, Clyde W. (Course Technology, 1996)
This book is divided into five parts: Decision making and knowledge; Foundations of decision support systems; Knowledge-management techniques for decision support; Artificially intelligent decision support systems; and Multiparticipant and executive decision support systems.